Réponses

2014-04-27T12:07:07+02:00
Bonjour
1)
H=(x-4)²-x(x-10)
H = x²-8x+16-x²+10x
H = 2x+16 
H(x) = 16  revient à 2x+16 = 16  pour x = 0 
2)
I = (7x-3)² - 5² 
I = (7x - 3 - 5)(7x - 3 + 5 )
I= (7x - 8)(7x + 2)  
I = 0 revient à 
(7x-8) = 0     pour x = 8/7    
ou
(7x +2) = o     pour x = -2/7 

Bonne journée
2014-04-27T12:33:05+02:00
1) H = (x – 4)² – x (x – 10)
a) (x² + 2x X 4 – 4²) – (x² – 10x)
     = (x² + 8x – 16) – (x² – 10x)
     = x² + 8x – 16 – x² + 10x
     = x² + x² – 8x – 10x + 16
     = x² – 18x + 16